Safety and Outcome of High Dose Parenteral Amino Acid Supplementation for VLBW Neonates on Partial Parenteral Nutrition: A Randomised Controlled Study - Rakesh Gami; Manisha Bhandankar (JCDR Research and Publications Pvt. Ltd., 2019)
Introduction: Total Parenteral Nutrition (TPN) is prescribed to meet a neonate's requirement for growth and development when his/her condition and/or gestation prevents complete enteral feeding. In India Partial Parenteral Nutrition (PPN) is used in neonatal units with inadequate facilities to prepare TPN. Aim: To evaluate the effect of supplementation of high dose parenteral Amino Acid (AA) on growth and biochemical parameters of Very Low Birth Weight (VLBW) neonates receiving PPN in first week of life. Materials and Methods: This was a Randomised controlled study, conducted in a tertiary care medical center. Sixty VLBW newborns with birth weight of <1500 gm admitted to level III NICU within 24 hour of life were included and Randomised into two groups of AA supplementation: One group received 1 g/kg/day of parenteral AA (Aminoven) on day 1, which was increased by 1g/kg/day till 4 gm/kg/day. The other group received 3 g/kg/day of parenteral AA on day 1, which was increased to 4 g/kg/day on the next day. Both the groups were continued on AA till they reached 75% of enteral feeds. Independent sample and chi-square test were used to analyse the data. Results: With similar baseline characteristics, serum sodium (p=0.001) and blood urea (p=0.041) levels were higher during 1st week of hospital stay. The daily physiological weight loss was more in neonates who received high AA from day 1 of life. There was no significant difference in weight gain (p>0.05) between the two groups during the hospital stay. The mean hospital stay was 23±4.5 days for Group A and 22.4± 3.6 days for Group B. Conclusion: Supplementation of high dose parenteral AA in VLBW infants receiving PPN does not help in weight gain during hospital stay, although well tolerated.